2002
DOI: 10.1128/jcm.40.8.2886-2892.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance of Four Genotypic Methods for Studying the Genetic Epidemiology of Aspergillus fumigatus Isolates

Abstract: In the present investigation, 49 Aspergillus fumigatus isolates obtained from four nosocomial outbreaks were typed by Afut1 restriction fragment length polymorphism (RFLP) analysis and three PCR-based molecular typing methods: random amplified polymorphic DNA (RAPD) analysis, sequence-specific DNA primer (SSDP) analysis, and polymorphic microsatellite markers (PMM) analysis. The typing methods were evaluated with respect to discriminatory power (D), reproducibility, typeability, ease of use, and ease of interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
63
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 41 publications
6
63
0
Order By: Relevance
“…However, our results may indicate that the three profiles found twice were actually from related isolates. Unfortunately, studies comparing different fingerprinting techniques for A. fumigatus show that, up to now, no single technique can be considered the "gold standard" (3,8). Additional fingerprinting of these isolates by AFLP analysis (18) also showed that these three pairs of isolates were indistinguishable from each other (results not shown).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, our results may indicate that the three profiles found twice were actually from related isolates. Unfortunately, studies comparing different fingerprinting techniques for A. fumigatus show that, up to now, no single technique can be considered the "gold standard" (3,8). Additional fingerprinting of these isolates by AFLP analysis (18) also showed that these three pairs of isolates were indistinguishable from each other (results not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Genotypic methods include several techniques, such as random amplified polymorphic DNA (RAPD) analysis (1,10,11), restriction fragment length polymorphism (RFLP) analysis (13), amplified fragment length polymorphism (AFLP) analysis (18), and microsatellite length polymorphism (2). The last technique is sometimes also called microsatellite polymorphism analysis (5) or polymorphic microsatellites marker analysis (8). However, a major problem with pattern-based techniques, such as RAPD, RFLP, and AFLP analyses, is the poor interlaboratory reproducibility.…”
mentioning
confidence: 99%
“…We used AFLP fingerprinting for determining the epidemiologic relatedness between the collected isolates. To date several other PCR fingerprinting methods have been described for A. fumigatus, but they either lack the necessary reproducibility between experiments (like Random Amplified Polymorphic DNA analysis [RAPD]) or require previous genomic information (like microsatellite analysis) (14). AFLP finger- printing, however, has proven to be a generic fingerprinting method with intrinsic superior reproducibility and a high degree of discriminatory power compared to other random amplification methods like RAPD (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous papers were published recently on the application of several typing techniques to A. fumigatus isolates, only some authors attempted to examine the reproductive mode of A. fumigatus populations and the conclusions drawn by them were controversial (Girardin et al 1994, Fridkin & Jarvis 1996, Lasker 2002, Levdansky et al 2007. In Latin America, there is very little information on these different aspects of the epidemiology of aspergillosis.…”
mentioning
confidence: 99%